SEORANG PENDERITA HIPOKALSEMIA BERAT OLEH KARENA HIPOPARATIROIDISME DIDAPAT - Dharmawan Harjanto, David; Ratna Saraswati, Made; Suastika, Ketut (journal of internal medicine, 2008)
Albeit rare, hypocalcemia might present an acute severe symptom as hypocalcemic seizure, which is documented in ourpatients. Failure in its diagnosis and management will lead to significant morbidity and mortality. Establishing the PTH status,anorganic-phosphate and magnesium level will enable investigation on possible etiology of hypocalcemia. The overall incidenceof post thyroidectomy hypoparathyroidism and hypocalcemia is about 0.5-3 % worldwide. The pathophysiology are multifactorial,it is not simply the glands extirpations, as well as its multiple risk factors although operator technique skill is still theprominent one. We have presented a case of 24 year old female with an acute generalized seizure (hypocalcemic seizure) andprolonged corrected QT interval due to a severe hypocalcemia secondary to hypoparathyroidism from a total thyroidectomy,accompanied by acquired hyperthyroidism and a cerebral cortex calcification. Clinical symptoms and total calcium were improvedafter intravenous calcium gluconate, followed by oral calcium and calcitriol administrations. However, the ideal therapyfor hypoparathyroidism is still the hormone substitution, either by auto/xeno-transplantations or injections, pending further studies.PTH level determinations immediately or several hours after surgery and thus oral calcium supplementations might predictand reduce the incidence of post thyroidectomy hypocalcemia and hypoparathyroidism.